EFFECTS OF ANESTHETIC STRATEGY ON PATIENTS’ OUTCOMES WITH ACUTE BASILAR ARTERY OCCLUSION UNDERGOING MECHANICAL THROMBECTOMY - AMJAD, MH; FAIZUDDIN, .; ALASMAR, O; AZIZ, A; TARIQ, M; FATIMA, .; KHAN, S (Biological and Clinical Sciences Research Journal, 2024)
The anaesthetic strategy employed during mechanical thrombectomy for patients with acute basilar artery occlusion (ABAO) has become a topic of great interest in recent years. Objective: The main objective of the study is to find the effects of anaesthetic strategy on patients’ outcomes with acute basilar artery occlusion undergoing mechanical thrombectomy. Methods: This retrospective observational study was conducted at Hameed Latif Hospital, Lahore, from January 2023 to September 2023. Data were collected from 85 patients divided into two groups based on the anaesthetic strategy used during the mechanical thrombectomy procedure. Group A consisted of patients who received general anaesthesia (n = 45), while Group B comprised those treated under conscious sedation (n = 40).Results: The time to procedure was significantly shorter in the CS group (28 ± 6 minutes) compared to the GA group (38 ± 7 minutes, p < 0.01). Both groups had similar procedure durations and revascularization success rates (80% for GA and 78% for CS, p = 0.8). In terms of functional outcomes, the CS group had a higher, though not statistically significant, percentage of patients with favorable mRS scores at 90 days (55% vs. 44%, p = 0.3). The GA group experienced higher rates of peri-procedural hypotension (24% vs. 10%, p = 0.05), while 90-day mortality rates were slightly lower in the CS group, but not significantly different (25% vs. 33%, p = 0.4). Conclusion: It is concluded that both general anaesthesia (GA) and conscious sedation (CS) are effective anaesthetic strategies for patients undergoing mechanical thrombectomy for acute basilar artery occlusion, with no significant difference in revascularization success or mortality.